Myelomatous pleural effusion as an initial presenting sign in a case of multiple myeloma - Sharma, Dinesh Chandra; Sharma, Deepanjali (International Journal of Research in Medical Sciences, 2020)
Multiple Myeloma (MM) is a neoplastic disease which mainly affects bone marrow but rarely may infiltrate extramedullary tissues as well. Myelomatous pleural effusions (MPE) develop due to extension of plasmacytoid cell lesions of thoracic bones into pleural tissue and directly presenting as an initial sign in a case of MM is exceedingly rare. It indicates poor prognosis, resistance to treatment and more chance of relapse in spite of aggressive chemo-radiotherapy. The effusions of serous cavities in MM generally develop as a late complication of the disease like heart failure, renal failure, pneumonia and amyloidosis. We are reporting a rare case of IgG subtype myelomatous pleural effusion demonstrating abundance of plasmacytoid cells in pleural fluid. Bone marrow smear examination favoured the diagnosis of multiple myeloma with the presence of predominant population of plasma cells with high cellularity. There were also presence of a heterogenous myelomatous mass lesion in the right infratemporal fossae, multiple erosive lesions in ribs, vertebral bodies, skull and pelvic bones. Pleural fluid and serum protein electrophoresis demonstrated the presence of gamma monoclonal protein peaks confirming the diagnosis.